Comparing Remote Heart Rate Accuracy Using Different Wavelengths - Ravindran S.; Weng L.Y.; Salleh Bin Mohamed Sahari K.; Anuar A.B.; Abdul Jalal M.F.B.; Bin Mohamad Rafaai Z.F.; Naidu A-P Raventhran P.; Mohd Radzi H.B.; Yussof S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Biomedical signal processing; Blood; Blood vessels; Heart; Hemodynamics; Image processing; Patient monitoring; Processing; Heart rate; Heart rate variability; Heart-rate; Heart-rate monitoring; Photoplethysmography; Remote-heart rate; Remote-photoplethysmography; RGB;; Photoplethysmography